2012
DOI: 10.1117/1.jbo.17.8.081417
|View full text |Cite
|
Sign up to set email alerts
|

Study of optical properties and proteoglycan content of tendons by polarization sensitive optical coherence tomography

Abstract: The highly orientated collagen fibers in tendons play a critical role for transferring tensile stress, and they demonstrate birefringent optical properties. However, the influence that proteoglycans (PGs) have on the optical properties of tendons is yet to be fully elucidated. PGs are the essential components of the tendon extracellular matrix; the changes in their quantities and compositions have been associated with tendinopathies. In this study, polarization sensitive optical coherence tomography (PS-OCT) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…This capability is particularly useful in biological tissue with regularly arranged fibrous architecture, such as collagen, that may induce form-birefringence and result in a measurable retardation signal. PS-OCT has been used to image collagen-rich tissues such as tendon and cartilage [4,5], the loss of birefringence signal in skin burns [6], and in ophthalmology, where it enables a more detailed interpretation of the retinal structures such as the birefringent retinal nerve fiber layer [7][8][9][10]. The birefringence signal measured with PS-OFDI has also been shown to correlate with collagen content of aortic plaques, which could serve as a predictor of plaque vulnerability [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This capability is particularly useful in biological tissue with regularly arranged fibrous architecture, such as collagen, that may induce form-birefringence and result in a measurable retardation signal. PS-OCT has been used to image collagen-rich tissues such as tendon and cartilage [4,5], the loss of birefringence signal in skin burns [6], and in ophthalmology, where it enables a more detailed interpretation of the retinal structures such as the birefringent retinal nerve fiber layer [7][8][9][10]. The birefringence signal measured with PS-OFDI has also been shown to correlate with collagen content of aortic plaques, which could serve as a predictor of plaque vulnerability [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Certain proteoglycans also modulate fibrillogenesis and fiber alignment (30). Studies have shown that removal of GAGs results in disorganization of collagen fibrils (31). GAGs present between collagen fibrils in connective tissues may aid their arrangement, resisting complete fiber disorganisation during stretching.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, PS-OCT was used to visualize the evolution of the collagen fiber alignment via birefringence in tissue-engineered tendons in response to varying growth environments and to investigate degenerative changes related to rupture in Achilles tendons [190,191]. Lately, the influence of proteoglycans-which are essential components of the tendon extracellular matrix associated with tendinopathies-on the optical properties of tendons have been studied by PS-OCT [192]. In skeletal muscle of genetically-altered (mdx) mice, exercise-induced ultrastructural changes were detected by PS-OCT in in vivo animals [193].…”
Section: Ps-oct In Muscles Tendons Cartilage and Bonementioning
confidence: 99%